CONSTRUCTAL THEORY APPLIED TO THE GEOMETRIC OPTIMIZATION OF ELLIPTICAL CAVITIES INTO A SOLID CONDUCTING WALL - Rocha, L. A. O.; Biserni, C.; Lorenzini, E. (Revista de Engenharia Térmica, 2008)
This work reports, according to Bejan’s Constructal theory, the geometric optimization of an elliptical cavity that intrudes into a solid conducting wall. The objective is to minimize the global thermal resistance between the solid and the cavity. There is uniform heat generation on the solid wall. The cavity is optimized for two sets of thermal conditions: isothermal cavity and cavity bathed by a steady stream of fluid. The solid conducting wall is isolated on the external perimeter. The total volume and the elliptical cavity volume are fixed while the geometry of the cavity is free to vary. The results show that the optimized geometrical shapes are relatively robust, i.e., insensitive to changes in some of the design parameters: the cavity shape is optimal when penetrates the conducting wall almost completely.